Integration of Christian Values in Digital Church Service Management: A Contextual Study at KGPM Sidang Syalom Tetey, North Minahasa in the Metaverse Era - Cristofan Muliku (Philosophy Global: International Journal of Christian and Catholic Philosophy, 2025)
The development of digital technology has changed the paradigm of church ministry from a conventional model to a more participatory digital and metaverse-based ministry. This study aims to analyze how Christian values are integrated into the digital ministry management of the KGPM Sidang Syalom Tetey Church, North Minahasa. Using a qualitative approach with a contextual case study method, this study explores the application of faith principles such as love, responsibility, honesty, loyalty, and servant leadership in the management of the church's digital ministry. The results show that digital ministry management in this church successfully combines technological innovation with Christian spirituality through the use of digital media, multimedia team coordination, and accountable online reporting. The integration of Christian values enables the church to carry out technologically relevant ministries without losing their ethical and spiritual dimensions. In the context of the metaverse era, churches face ethical, relational, and spiritual challenges, but also gain new mission opportunities to expand their ministry across geographical boundaries. The theological implications of this study emphasize the importance of theological discernment and spiritual accountability in directing the use of technology as a means of mission, not as an end in itself. Thus, the church is called to be an ethical and prophetic agent in the midst of digital transformation, making technology a tool to glorify Christ and strengthen the faith life of the congregation.